2019
DOI: 10.3389/fpsyg.2019.02458
|View full text |Cite
|
Sign up to set email alerts
|

Facial Expression Processing Is Not Affected by Parkinson’s Disease, but by Age-Related Factors

Abstract: The question whether facial expression processing may be impaired in Parkinson’s disease (PD) patients so far has yielded equivocal results – existing studies, however, have focused on testing expression processing in recognition tasks with static images of six standard, emotional facial expressions. Given that non-verbal communication contains both emotional and non-emotional, conversational expressions and that input to the brain is usually dynamic, here we address the question of potential facial expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 85 publications
1
1
0
Order By: Relevance
“…The rates of individuals with difficulty recognizing people they saw every day and asking an unrecognized person to remove their mask to recognize them were higher in the PwP group than in the YHC group, but there was no statistically significant difference between the OHC and YHC groups. These findings are consistent with the results of another study that compared PwP, OHC, and YHC groups in terms of recognizing facial expressions on a video 22 . However, in contrast to that study evaluating tasks using holistic processing, we assessed a challenging aspect of daily life that emphasizes feature-based processing, which is reportedly intact in individuals over the age of 50 years.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The rates of individuals with difficulty recognizing people they saw every day and asking an unrecognized person to remove their mask to recognize them were higher in the PwP group than in the YHC group, but there was no statistically significant difference between the OHC and YHC groups. These findings are consistent with the results of another study that compared PwP, OHC, and YHC groups in terms of recognizing facial expressions on a video 22 . However, in contrast to that study evaluating tasks using holistic processing, we assessed a challenging aspect of daily life that emphasizes feature-based processing, which is reportedly intact in individuals over the age of 50 years.…”
Section: Discussionsupporting
confidence: 91%
“…Derya et al reported that the PwP performed similar to their peers in detecting facial expression shown on a video whereas they were at a disadvantage when asked to recognize facial expressions from photographs in a laboratory task 22 . When this finding is evaluated together with the results of previous studies reporting a disconnection of the pathways extending from the prefrontal region to the ventral and dorsal pathways of visual processing in PwP 23 , the PwP performing similar to their peers in recognizing facial expressions in a more dynamic circumstance of a video may indicate that the dorsal pathway associated with dynamic processes is less affected in PD.…”
Section: Discussionmentioning
confidence: 99%